Preparation of recombinant myoglobin and investigation of the liquid antigen stability for quality control materials - Yu-Hui Wang; Xi-Feng Sun; Chun-Xin Xu; Feng-Qiang Sun; Rong-Rong Wang; Xiao-Kun Bian; Zhan-Zhao Wang; Qiang Wu (Practical Laboratory Medicine)
Myoglobin (Mb) has been used as a biomarker for acute myocardial infarction. This study aimed to evaluate the stability of liquid Mb as quality control materials for Mb determination. Mb protein was expressed in Escherichia coli system and purified using Ni2+ chelate affinity chromatography. The purity of purified recombinant Mb reached to 95 %. The immunoreactivity of Mb was investigated using Mb assay kits. The coefficient of determination (R2) of the curve fitted with dilution ratio and Mb concentration as variables was greater than 0.95, which indicated that Mb had good immunoreactivity. The concentrations per gradient measured using different kits had no significant difference (p-value>0.05), which indicated that the reactivity between the Mb antigen and Mb antibodies with different epitopes was good. The effects of different storage buffer, storage temperature and storage times on the stability of liquid Mb were investigated by detecting the concentration changes. At 2–8 °C for two months, Mb concentration in buffer B (Tris-HCl, pH 7.8, containing 1 % BSA and 0.05 % NaN3) decreased within 10 % compared with the initial concentration. The long-term storage stability was investigated by the thermal acceleration experiment. At 37 °C for one week, Mb concentration decreased by less than 15 %, indicating that the Mb had good long-term storage stability. The prepared liquid Mb had good immunoreactivity and stability, avoiding storage in freeze-dried powder. It was a promising alternative as the quality control material for Mb detection.